Gene Enrichment Analysis Reveals Major Regulators of Mycobacterium tuberculosis Gene Expression in Two Models of Antibiotic Tolerance - Matern, William M.; Rifat, Dalin; Bader, Joel S.; Karakousis, Petros C. (Frontiers in Microbiology, 2018)
The development of antibiotic tolerance is believed to be a major factor in the lengthy duration of current tuberculosis therapies. In the current study, we have modeled antibiotic tolerance in vitro by exposing Mycobacterium tuberculosis to two distinct stress conditions: progressive hypoxia and nutrient starvation (PBS). We then studied the bacterial transcriptional response using RNA-seq and employed a bioinformatics approach to identify important transcriptional regulators, which was facilitated by a novel Regulon Enrichment Test (RET). A total of 17 transcription factor regulons were enriched in the hypoxia gene set and 16 regulons were enriched in the nutrient starvation, with 12 regulons enriched in both conditions. Using the same approach to analyze previously published gene expression datasets, we found that three M. tuberculosis regulons (Rv0023, SigH, and Crp) were commonly induced in both stress conditions and were also among the regulons enriched in our data. These regulators are worthy of further study to determine their potential role in the development and maintenance of antibiotic tolerance in M. tuberculosis following stress exposure.